SRUKTUR LISĀN ARAB: Memahami Pengertian Al-Qur`an sebagai Lisān ‘Arabiy - Sugeng Sugiyono (Adabiyyāt: Jurnal Bahasa dan Sastra, 2008)
The speculation on the fact that Quranic language consists of 'ajam or non-Arab languages as well as dialects (lahjah, qira’āt) has been an issue on the matter of Quranic language. Yet, the Koran confirms itself that it was revealed as “lisānin arabiyyin mubīnin”. This paper aims at describing the terminology. It can be concluded that “Lisān Araby” is a mixture of Arabic eastern and western dialects. The nonArabic languages (‘ajam) have adapted the Arabic pattern and structure thus they has fused with Arabic, known as lahjah or Quraish dialects.